Analysis of goal scoring patterns in the 2018 FIFA World Cup - Kubayi, A. (Journal of Human Kinetics, 2020)
Analysis of Goal Scoring Patterns in the 2018 FIFA World Cup by Alliance Kubayi1The aim of this study was to analyse the goal scoring patterns during the 2018 FIFA World Cup. All goals scored during the tournament were analysed using the InStat video analysis system. The results showed that 169 goals (open play: 60.9%; set play: 39.1%) were scored during the competition. While 85 goals (82.5%) were scored from elaborate attacks, 18 goals (17.5%) came from counter attacks. A chi-square test indicated that there was a significant difference in the type of possession (Chi2 (1, n = 103) = 43.58, p = 0.00). The highest number of goals was yielded from the final third (35%) as compared to the first (33%) and middle (32%) thirds. The results also indicated that most goals accounted from short passes (69.9%), while 13.6% of goals came from long passes and 16.5% from mixed passes (Chi2 (2, n = 103) = 62.12, p = 0.00). Soccer coaches should incorporate set pieces in their training sessions in view to improve goal-scoring opportunities. Key words: goals, set pieces, open play, tactics, performance.